THE TRADITION OF CUTTING THE FINGERS OF THE DANI TRIBE AS A SYMBOL OF MORNING LOCATED IN PAPUA - Andira Devi Dwi Ayu; Izat Rolibi Putra Amin; Diandra Diandra Alya Sayyidina; Adela Adela Oktaviani Putri; Reihan Reihan Cahya Ardhika (Omnibus Law Journal, 2022)
Customary is a habit or it can also be called a culture that has been carried out continuously and repeatedly, which has become the hallmark of a place or area that contains cultural values, norms, institutions, and habits. Customary law itself regulates all behavior carried out by people in a particular community group. Adat itself is divided into 2 (two) kinds, namely custom which if someone does it and is said to have violated it and ends up giving sanctions it is called customary law, while adat which if someone does it and does not include violating activities is called habit. Customary law is a habit carried out by a community that has various binding rules and also includes unwritten law because it is not included in the legal record that arises from habits carried out for generations. Causing legal consequences if someone's behavior is said to be in violation, such as the iki paleg tradition carried out by the Dani Tribe. The conclusion obtained is that the tradition can be said not to violate if the person does it voluntarily, and can be classified as a violation of human rights if the person does it under coercion. Keywords: Customary Law, Human Rights (HAM), Dani Tribe.